Hereditary orotic aciduria with epilepsy and without megaloblastic anemia - Grohmann-Held, Karina; Hoffmann, Georg F. (Neuropediatrics, 2015)
Hereditary orotic aciduria is a rare metabolic disease that results from a defect of uridine-5-monophosphate synthase (UMPS). In affected patients, main clinical symptoms are a markedly increased urinary excretion of orotic acid combined with megaloblastic anemia. This report describes a new case of UMPS deficiency without megaloblastic anemia but with epilepsy.
Gesehen am 28.07.2017